2015
DOI: 10.1109/tcst.2014.2384002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Estimation of the Humans' Effect on the CO<sub>2</sub> Dynamics Inside a Conference Room

Abstract: We develop a data driven, partial differential equation-ordinary differential equation model that describes the response of the carbon dioxide (CO 2 ) dynamics inside a conference room, due to the presence of humans, or of a user-controlled exogenous source of CO 2 . We conduct three controlled experiments to develop and tune a model whose output matches the measured output concentration of CO 2 inside the room, when known inputs are applied to the model. In the first experiment, a controlled amount of CO 2 ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 45 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…In [3], [37]- [41] the indoor CO2 concentration is assumed to be uniform, and in [37]- [40] the length of time horizon l = 1, which implies that indoor CO2 concentration is with Markov property (memoryless property ). However, [42] showed that the gradient of indoor CO2 concentration can be very large, and CO2 emitted by certain occupant cannot be immediately sensed. Therefore, it is unreasonable to simply set l = 1 unless the sampling time is large enough.…”
Section: Indoor Occupancy Estimation From Co2 Datamentioning
confidence: 99%
“…In [3], [37]- [41] the indoor CO2 concentration is assumed to be uniform, and in [37]- [40] the length of time horizon l = 1, which implies that indoor CO2 concentration is with Markov property (memoryless property ). However, [42] showed that the gradient of indoor CO2 concentration can be very large, and CO2 emitted by certain occupant cannot be immediately sensed. Therefore, it is unreasonable to simply set l = 1 unless the sampling time is large enough.…”
Section: Indoor Occupancy Estimation From Co2 Datamentioning
confidence: 99%
“…For example, CO 2 sensor has been deployed to infer the number of people in a zone [5]. Although there is a response time of the sensor to human movements, careful calibration can be done based on PDE framework to achieve good modeling.…”
Section: A Presence Sensor and Occupancy Sensingmentioning
confidence: 99%
“…For example, CO 2 sensor has been deployed to infer the number of people in a zone [22]. Although there is a response time of the sensor to human movements, careful calibration can be done based on PDE framework to achieve good modeling.…”
Section: A Presence Sensor and Occupancy Sensingmentioning
confidence: 99%